Racial Discrimination Portrayed in The American Society of Magical Negroes (2024) (Sastra Inggris UNPAM, 2025)
This study focuses on racial discrimination in The American Society of Magical Negroes (2024) movie directed by Kobi Libii. This is a satirical movie about a secret society where black people, like the main character Aren, are expected to solve white people’s problems while neglecting their own needs. Aren begins to question this role, challenging the idea that black people exist only to serve others. This study aims to analyze racial discrimination portrayed in this movie, it also aims to analyze how the main character deals with it. A qualitative analysis method is utilized in this study, with a focus on interpreting the movie’s narratives and characters. The theory used in this study is Critical Race Theory by Delgado & Stefancic (2001). The study’s findings show two types of discrimination such as stereotypes and exploitation, this study also identifies three ways character resist such as acting as Magical Negro, counter-storytelling, and rebellion.